THE EFFECT OF FOOTBALL TRAINERS’ COACHING AGE ON LEADERSHIP STYLE - DURMUŞOĞLU, Mehmet Vakıf (Journal of ROL Sport Sciences, 2021)
The aim of this research is to examine the effect of coaching age of football coaches on leadership styles (educational behavior, democratic behavior, autocratic behavior and social support behavior) and to examine these data in terms of age variable. The research group consists of 269 participants. The Leadership in Sports Scale (SLÖ) aims to measure four different leadership behaviors of the coach towards the perception of the athlete. The "Leadership in Sports Scale" developed by Toros and Tiryaki (2006) was used to collect the data. According to the results of the research, while there was no significant difference in educational and didactic behavior and autocratic behavior; Significant differences in democratic and social support behaviors were reached at the age of 1-5 sports. In the light of the findings it is thought that on the effect of coaching age of football coaches on leadership style Democracy and social support behavior sub-dimension of coaches aged 1-5 in sports is understandably high in educational and didactic behavior and autocratic behavior sub-dimensions.